Data file 3. Raw sequencing data statistics - Jeanne Arline Rajaonarivelo (17282572) (2025)
Here, we produced the most complete, high quality genome assembly of L. loa derived from a single female adult worm collected from a patient originating from Cameroon. We used Oxford Nanopore Technologies (ONT) sequencing to generate long reads that fill gaps in the previously published genome and enhance the quality of data.